A responsabilidade social na Costa Rica - Alvarado, Mariangel Sánchez (2018)
The study presents the historical and contextual elements to understand the Social Responsibility from a critical analysis. By means of the dialectic method history, it is intended to make an approach from the whole of the object to understand it in addition to its potential. First of all, the "reform" which had the status in the 1980s, based on the needs of the capitalist mode of production to their reproduction and how it was deploying in the governments of Latin America. Subsequently, there is a characterization of the Social Responsibility initiatives in the world and in Latin America with the aim to understand its structure and articulated configuration to the historical conditions that gave rise to this; this part is important to know the theoretical guidelines that each country has placed by international bodies, which standardize the performances of each country. In the same line, the case of Costa Rica is specifically examined, based on its characterization as a country, its historic setting and understanding how the Social Responsibility was installed in this country through the influence of other countries, especially from Europe. Social Responsibility is understood as one of the factors that leverages the bourgeois hegemony and that is a strategy of rearticulation of corporate actions and a new consensus bourgeois of political-ideological cutting and fundamentally economical, is, without doubt, a strategy which potentiate the valorization of capital, therefore, it cannot be conceived as a way of improving the inefficiency of the State by means of shared responsibilities, if not that goes beyond this conservative discouRS that most companies and international organizations in this field has as its foundation. As the analysis performed, it can be noted that in Costa Rica despite the existence of a National Policy of Social Responsibility that involves private companies, the State and civil society organizations, still have weaknesses in what refers to its articulation that has hampered its materialization.